Drug Utilization Study and Adverse Drug Reaction Reporting among Patients Using Anticoagulants in a Tertiary Care Teaching Hospital - Alzubaidi, Nafaa; Sharma, Manju; Abdulmalik, Watheeq; Habib, Anwar; Alhalmi, Abdulsalam (Journal of Drug Delivery and Therapeutics, 2019)
Drug utilization (DU) is systematic regulatory approach designed to identify diversity of drugs use and to evaluate the rational use of medicines in population. Anticoagulants are drugs used to avoid thrombus extension and embolic consequences with associated risks related to their administration. Objectives: The objectives of the present study were to evaluate the drug prescription pattern of anticoagulants, observe and report drug interactions and adverse drug reactions among patients using anticoagulants. Method: Utilization of anticoagulant drugs was evaluated in 50 patients from 4 wards (dialysis, medicine, orthopedic and intensive-care unit) of a tertiary care teaching hospital in a cross-sectional, prospective study conducted for 4 months i.e. from 1st January 2018 to 30th April 2018. Results: LMWH (enoxaparin) was the maximum preferred parenteral anticoagulant prescribed to 31 % of patients as prophylaxis for deep vein thrombosis followed by heparin. 14(28%) of total population were administered combination therapy and 36 (72%) patients received only one anticoagulant drug during hospitalization. The most prescribed drug combination was enoxaparin+warfarin followed by enoxaparin+acenocoumarol. For discharge medicines, 14 patients were prescribed oral anticoagulants; 9 (64.3%) patients were prescribed with warfarin and the remaining 5 (35.7%) patients were given acenocoumarol. 28(56%) patient’s laboratory tests were evaluated for parameters like prothrombine time (PT) and international normalized ratio (INR). In the remaining 22(44%) patients, the above tests were not performed. Sixteen drug interactions were identified, ten were pharmacodynamics and the rest six were pharmacokinetic interactions. Three adverse drug reactions were reported during the study. The need for dosage adjustment in different diagnostic situations or specific populations is very crucial. Conclusion: The therapy with these drugs needs to be cost effective and reduce the complications associated with their use.Keywords:  Anticoagulants, Drug utilization evaluation, Drug interactions.